Ultrarapid Delayed Rectifier K+ Channelopathies in Human Induced Pluripotent Stem Cell-Derived Cardiomyocytes - Hilderink, Sarah; Devalla, Harsha D.; Bosch, Leontien; Wilders, Ronald; Verkerk, Arie O. (Frontiers in Cell and Developmental Biology, 2020)
Atrial fibrillation (AF) is the most common cardiac arrhythmia. About 5–15% of AF patients have a mutation in a cardiac gene, including mutations in KCNA5, encoding the Kv1.5 α-subunit of the ion channel carrying the atrial-specific ultrarapid delayed rectifier K+ current (IKur). Both loss-of-function and gain-of-function AF-related mutations in KCNA5 are known, but their effects on action potentials (APs) of human cardiomyocytes have been poorly studied. Here, we assessed the effects of wild-type and mutant IKur on APs of human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs). We found that atrial-like hiPSC-CMs, generated by a retinoic acid-based differentiation protocol, have APs with faster repolarization compared to ventricular-like hiPSC-CMs, resulting in shorter APs with a lower AP plateau. Native IKur, measured as current sensitive to 50 µM 4-aminopyridine, was 1.88±0.49 (mean±SEM, n=17) and 0.26±0.26 pA/pF (n=17) in atrial- and ventricular-like hiPSC-CMs, respectively. In both atrial- and ventricular-like hiPSC-CMs, IKur blockade had minimal effects on AP parameters. Next, we used dynamic clamp to inject various amounts of a virtual IKur, with characteristics as in freshly isolated human atrial myocytes, into 11 atrial-like and 10 ventricular-like hiPSC-CMs, in which native IKur was blocked. Injection of IKur with 100% density shortened the APs, with its effect being strongest on the AP duration at 20% repolarization (APD20) of atrial-like hiPSC-CMs. At IKur densities <100% (compared to 100%), simulating loss-of-function mutations, significant AP prolongation and raise of plateau were observed. At IKur densities >100%, simulating gain-of-function mutations, APD20 was decreased in both atrial- and ventricular-like hiPSC-CMs, but only upon a strong increase in IKur. In ventricular-like hiPSC-CMs, lowering of the plateau resulted in AP shortening and triangulation. We conclude that a decrease in IKur, mimicking loss-of-function mutations, has a stronger effect on the AP of hiPSC-CMs than an increase, mimicking gain-of-function mutations, whereas in ventricular-like hiPSC-CMs such increase results in AP shortening and triangulation, causing their AP morphology to become more atrial-like. Effects of native IKur modulation on atrial-like hiPSC-CMs are less pronounced than effects of virtual IKur injection because IKur density of atrial-like hiPSC-CMs is substantially smaller than that of freshly isolated human atrial myocytes.